Nietzsche : a complete introduction - Jackson, Roy, 1962- (Teach yourself books., 2014)
It covers the key areas that higher-education students are expected to be confident in, outlining the basics in clear jargon-free English, and then providing added-value features like summaries of key books, and even lists of questions you might be asked in your seminar or exam. The book uses a structure that mirrors the way Nietzsche is studied on many university courses, with chapters looking at Nietzsche's life, The Birth of Tragedy, the revaluation of all values, the will to power, Thus Spoke Zarathustra, truth and perspectivism, religion, politics, and Nietsche's legacy.